miRNAs are Essential for the Survival and Maturation of Cortical Interneurons - Tuncdemir, Sebnem N. (Cereb Cortex, 2015)
Complex and precisely orchestrated genetic programs contribute to the generation, migration, and maturation of cortical GABAergic interneurons (cIN). Yet, little is known about the signals that mediate the rapid alterations in gene expression that are required for cINs to transit through a series of developmental steps leading to their mature properties in the cortex. Here, we investigated the function of post-transcriptional regulation of gene expression by microRNAs on the development of cIN precursors. We find that conditional removal of the RNAseIII enzyme Dicer reduces the number of cINs in the adult mouse. Dicer is further necessary for the morphological and molecular maturation of cINs. Loss of mature miRNAs affects cINs development by impairing migration and differentiation of this cell type, while leaving proliferation of progenitors unperturbed. These developmental defects closely matched the abnormal expression of molecules involved in apoptosis and neuronal specification. In addition, we identified several miRNAs that are selectively upregulated in the postmitotic cINs, consistent with a role of miRNAs in the post-transcriptional control of the differentiation and apoptotic programs essential for cIN maturation. Thus, our results indicate that cIN progenitors require Dicer-dependent mechanisms to fine-tune the migration and maturation of cINs.